The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1136/bmjdrc-2015-000116
|View full text |Cite
|
Sign up to set email alerts
|

Improving preparedness of medical students and junior doctors to manage patients with diabetes

Abstract: ObjectiveNew medical graduates are the front-line staff in many hospital settings and manage patients with diabetes frequently. Prescribing is an area of concern for junior doctors, however, with insulin prescribing reported as a particular weakness. This study aimed to produce an educational intervention which aimed to improve preparedness to manage patients with diabetes and evaluate it using a mixed methods approach.Research design and methodsAn e-resource (http://www.diabetesscenariosforjuniordoctors.co.uk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“… 5 , 6 A study by the University of Exeter Medical School used an online resource to qualitatively improve new doctors’ lack of confidence in managing patients with diabetes. 7 These examples demonstrate a recognized need to improve confidence in clinical diabetes mellitus management.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 A study by the University of Exeter Medical School used an online resource to qualitatively improve new doctors’ lack of confidence in managing patients with diabetes. 7 These examples demonstrate a recognized need to improve confidence in clinical diabetes mellitus management.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study determined that an online bank of diabetes-based clinical cases could address junior doctors’ confidence in managing patients with diabetes. 24 In a study previously published by our group, it was demonstrated that a preclerkship Diabetes Enrichment Elective improved medical students’ confidence in specific aspects of DSMES discussions with patients. 22 The current study differs from our previous one in that it assesses the effectiveness of various training modalities in this area versus a single modality evaluated previously.…”
Section: Discussionmentioning
confidence: 95%
“…Arguably, this may not necessarily be the best instructional method. Previous studies have stressed the importance of providing opportunities to work with authentic clinical scenarios in a safe environment, which can ameliorate junior doctors’ lack of confidence to manage patients with drugs …”
Section: Discussionmentioning
confidence: 99%